Alcohol-related cognitive mechanisms underlying adolescent alcohol use and alcohol problems: Outcome expectancy, self-schema, and self-efficacy. (June 2020) - Lee, Chia-Kuei; Corte, Colleen; Stein, Karen F.; Feng, Jui-Ying; Liao, Li-Ling
Highlights: Theoretical model for the functional relationship among the alcohol-related cognitions were supported. Alcohol-related cognitive constructs predicted adolescent alcohol use and problems. Alcohol-related self-schema and self-efficacy mediated alcohol expectancy effects. Abstract: Purpose: The objective of this study was to empirically test a theoretical model to determine the cognitive mechanisms that are associated with adolescent alcohol use and alcohol problems. We posited that alcohol outcome expectancies would affect alcohol-refusal self-efficacy through the drinker self-schema. We also posited that alcohol outcome expectancies and the drinker self-schema would affect alcohol use and problems through alcohol-refusal self-efficacy. Methods: A survey was administered to 225 adolescents in a public junior high school in Taiwan at two-time points, six months apart. Path analysis was used to determine the mechanisms underlying the alcohol-related cognitive constructs on the alcohol use and alcohol problems separately, controlling for appropriate alcohol-related personal and environmental factors. Indirect effects were estimated using the bootstrapping method. Results: Higher positive alcohol outcome expectancies and lower negative alcohol outcome expectancies predicted higher drinker self-schema scores. Higher positive alcohol outcome expectancies and drinker self-schema scores predicted lower alcohol-refusal self-efficacy. Lower alcohol-refusal self-efficacy was associated with a history of drinking and alcohol problems in the past six months. Effects of alcohol outcome expectancies on alcohol use and alcohol problems were partially mediated through the drinker self-schema and alcohol-refusal self-efficacy. Conclusions: Findings support the proposed theoretical cognitive mechanisms underlying alcohol use and alcohol problems in a sample of Taiwanese adolescents. Given that alcohol-related cognitive constructs are modifiable, the findings also provide a foundation to suggest that interventions to reduce positive alcohol outcome expectations and prevent the formation of a drinker self-schema may facilitate alcohol-refusal self-efficacy and mitigate drinking behaviors in this adolescent population.